Relationship between anticipation and kinematic parameter in tennis serve - Fukubayashi, T.; Ogata, T. (Sport Science Research, 2014)
Skilled tennis players can predict ball direction even before the opponent`s racket-ball contact. Such a superior anticipatory performance depends on the visual information that is available from the essential kinematics of opponent`s motion. The aim of this study is to clarify the relationship between tennis server`s kinematic pattern and receiver`s anticipation performance by using multiple regression analysis with the racket parameter (explanatory variable) anticipated ball direction (dependent variable). 23 participants (10 expert players and 13 novices) voluntarily participated in the experiment. They were asked to response the serve direction to a live-action video clip of the model tennis server. Test serve was performed by two professional tennis players in the deuce side aiming at two targets on the service box (center and wide). The test films were occluded when the foot of the participants touched one of two mat-switches. The participants viewed 40 video clips and they scored their anticipatory judgment of the ball direction on a visual analogue scale (VAS), respectively. The result of multiple regression analysis, motion parameters of racket explained ball direction. These results indicated that experts and novices were able to pickup anticipatory cue. The anticipatory cue is the information of the motion parameters of server`s racket.